Penerapan Evidence Based Practice Hipertensi dengan Penerapan Teknik Relaksasi Benson - Lontoh, Esther; Kairupan, Michelle; Mokoginta, Fitri Angraini (Yayasan Syalom Cipta Sumikolah, 2025)
The estimated number of cases of hypertension in Indonesia is 63,309,620 people. According to the 2018 National Health Research (Riskesdas) report, approximately 34.11% of the population ≥ 18 years old suffers from hypertension (Ministry of Health of the Republic of Indonesia, 2019). Across Indonesia's 34 provinces, this condition can trigger various unexpected problems, such as threatening realities and increasing the risk of heart disease, stroke, and even death. The North Sulawesi Provincial Health Office explained that cases of hypertension in North Sulawesi reached 32,742 cases. This report uses case studies, nursing care provided using electrolyte fluid therapy and medication to address fluid balance and reduce pain, as well as pain management using Benson relaxation techniques, which can also help reduce pain. The results of the study found that acute pain problems are associated with increased cerebral vascular pressure. Sleep pattern disturbances are associated with psychological injury agents. Anxiety is related to lack of exposure to information about the disease process. The final results showed reduced headaches, complaints of insomnia began to improve, and feelings of anxiety and worry have decreased. In conclusion, fluid therapy, medication, and Benson relaxation techniques can address pain, sleep disturbances, and anxiety. Families are advised to maintain and monitor their health at the nearest hospital or community health center.